Factors affecting the perception and intention of Singaporeans to adopt mHealth application: An Empirical study - Chan, Soon Chee (2023)
This research provides empirical evidence on the relationship among various factors which affect the intention of mobile health application(mHealth) adoption among Singaporean users. Mobile Health applications have become ubiquitous in the healthcare industry, covering a wide range of disease and clinical use cases.